Leukoencephalopathy with brain stem and spinal cord involvement and high lactate: A genetically proven case with distinct MRI findings - İŞAK, BARIŞ; GÜNAL, DİLEK; ULUÇ, KAYIHAN; AĞAN YILDIRIM, KADRİYE (ELSEVIER SCIENCE BV, 2008)
Leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation (LBSL) is a recently described disorder with autosomal recessive mode of inheritance. Lately, mutations in the DARS2 gene, which encodes mitochondrial aspartyl-tRNA synthetase, have been found as the underlying defect. We report a 19-year-old male patient with cerebellar, pyramidal and dorsal column dysfunctions and specific magnetic resonance imaging (MRI) and characteristic magnetic resonance spectroscopy (MRS) abnormalities. The patient was compound-heterozygous for two mutations in DARS2. MRI showed selective involvement of cerebral and cerebellar white matter and superior and inferior cerebellar peduncles, without contrast enhancement. The U-fibers were spared. The sensory and the pyramidal tracts were affected over their entire length. Involvement of the intraparenchymal trajectories of the trigeminal nerves and mesencephalic trigeminal tracts was demonstrated. In the spinal cord, signal abnormalities were identified in the dorsal columns and the lateral corticospinal tracts. Proton-MRS of the frontal and cerebellar white matter showed elevated lactate, reduced N-acetylaspartate, increased myoinositol and mildly elevated choline. In LBSL, distinct MRI findings should lead to the diagnosis, which can be confirmed by the analysis of the disease gene DARS2. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: leukoencephalopathy; brain stem and spinal cord involvement; lactate elevation; DISEASE